Measuring the cost of consulting services under the traditional cost approach and the performance-based costing technique and its impact on achieving profits : Applied research in the advisory office of Al-Khwarizmi College of Engineering - University of Baghdad (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract:                    This research aims to apply the Performance Focused Activity Based Costing System in the consultant office of Al-Khwarizmi College of Engineering at the University of Technology for the purpose of measuring the cost of consulting services provided by these offices in order to reduce costs and their reflection in achieving profits. For the purpose of calculating costs accurately, and to test the hypothesis of the research, the research was applied in the office of the consultant of the College of Engineering Al-Khwarizm - University of Baghdad through the financial statements for the year ending 12/31/, because the data of these years were issued and audited by the Federal Office of Financial Supervision. A number of conclusions were reached, the most important of which are: reliance on traditional costing methods and techniques in measuring the cost of its services, which makes it unable to keep pace with developments in the business environment, as a result of its failure to properly determine the cost of its services, which is reflected negatively on profits. In addition, the use of costing technology based on activity based on performance would reduce costs, and help the management of these offices to continue to perform their work for a period of years.